AB1024 Clinically "Silent" Synovitis: Detected by Fluorescence Optical Imaging of the Hands & Wrists. (10th June 2014) - Kisten, Y.; Györi, N.; Rezaei, H.; Karlsson, A.; Romanus, C.; af Klint, E.; van Vollenhoven, R.
Abstract : Background: The detection of sub-clinical synovial inflammation ("silent synovitis") would be of critical importance for the detection of rheumatoid arthritis (RA) & other inflammatory arthritides, in its earliest pathophysiological stage ("pre-RA"). It has been suggested that ultrasound (US) with power or colour Doppler, can be a useful technology to achieve this. Ultrasound however, requires specially trained/skilled operators. Fluorescence optical imaging (FOI, "Rheumascan") is a novel imaging modality based on the use of an intravenous fluorescence dye, that allows imaging of the hands & wrists, with increased focal optical signal intensities in areas of high perfusion &/or capillary leakage. This diagnostic tool, is operator independent, & can be well carried out by a rheumatology nurse. Objectives: Here, we investigated whether FOI (Rheumascan) could be used in lieu of US (colour Doppler) for ascertaining hand & wrist sub-clinical synovitis. Methods: A total of 748 hand & wrist joints (6 wrist, 10 MCPs, 10 PIPs & 8 DIPs) in 22 patients (7 male & 15 female), aged between 19 & 84 years, with inflammatory arthritis (RA:9, JIA, polyarthritis, psoriatic arthritis, SLE & other diagnoses, 1-2 each) were examined clinically, by US & FOI. Joints were considered clinically inflamed when both swollen and tender, & non-inflamed otherwise. Ultrasound was considered positive for "active" synovitis if both thickening on grey scale & Doppler signals were present. FOI was considered positive in joints that displayed focal signal intensities, by visual inspection of recorded images & video clips. Results: Out of 748 joints evaluated, 72 (10%) were considered inflamed by clinical examination and 676 (90%) were not. Of the clinically non-inflamed joints, exactly 95 (14%) were inflamed by US. Of these joints, 72 (76%) were inflamed by FOI and 23 (24%) were not. Thus, the sensitivity of FOI for detecting clinically "silent" synovitis when defined as a positive US in the absence of clinical inflammation was 76%. Out of the 581 joints that were non-inflamed clinically and non-inflamed by ultrasound, 24 (4%) had inflammation by FOI, yielding a specificity of 96% (557/581). Conclusions: Under the assumption that US can correctly identify sub-clinical synovitis in clinically non-inflamed joints (using the combination of clinical examination & US as the "gold standard"), the sensitivity of FOI for detecting clinically "silent synovitis" in the hands & wrists is 76% and the specificity 95%. These metrics suggest that it may be a useful diagnostic tool in the setting of identifying patients with very early synovial inflammation of the hands &/or wrists. Acknowledgements: To all the patients & participants of the study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2215